Central nifedipine-induced alterations in salivary flow and compounds: Role of nitric oxide - Saad, Wilson Abrão [UNESP]; Guarda, Ismael Francisco Motta Siqueira; Camargo, Luiz Antonio de Arruda [UNESP]; Santos, Talmir Augusto Faria Brizola dos; Simões, Sylvio; Saad, William Abrão (Science Alert, 2006)
The aim of this study was to examine the role of nifedipine and Nitric Oxide (NO) on salivary flow and compounds (salivary amylase, saliva total proteins, saliva calcium, sodium and potassium). Male Holtzman rats weighting 200-250 g were anesthetized with zoletil 50 mg kg -1 (tiletamine chloridrate 125.0 mg and zolazepan chloridrate 125.0 mg) into quadriceps muscle and stainless steel cannulas were implanted into their lateral ventricle of the brain (LV). Animals in divided group were injected with nifedipine (50 μg μL -1) alone and in combination with 7-nitroindazol (7-NIT) (40 μg μL -1), neuronal NO Sinthase Inhibitor (nNOSI) and Sodium Nitroprussate (SNP) (30 μg μL -1) NO donor agent. As a secretory stimuli, pilocarpine dissolved in isotonic was administered intraperitoneally (ip) at a dosage of 10 mg kg -1 body weight. Saliva was collected for 7 min with four cotton balls weighing approximately 20 mg each, two of which were placed on either side of the oral cavity, with the other two placed under the tongue. Nifedipine treatment induced a reduction in saliva secretion rate and concentration of amylase, total protein and calcium without changes in sodium and potassium concentration in comparison with controls. Co-treatment of animals with nifedipine and SNP retained flow rate and concentration of amylase, total protein and calcium in normal levels. Co-treatment of animals with nifedipine and 7-NIT potentiated the effect of nifedipine on the reduction of saliva secretion and concentrations of amylase, total protein and calcium. Nifedipine (dihydroperidine) calcium-channel blocker widely in use is associated with salivary dysfunction acting in the central nervous system structures. NO might be the mechanism for protective effect against the nifedipine-induce salivary dysfunction, acting in the CNS. © 2006 Asian Network for Scientific Information.
Keywords: Blood pressure; Lateral ventricle; Nifedipine; Nitric oxide; Saliva; Water intake; 7 nitroindazole; amylase; calcium; isotonic solution; nifedipine; nitric oxide; nitric oxide donor; nitric oxide synthase inhibitor; nitroprusside sodium; pilocarpine; potassium; saliva protein; sodium; stainless steel; telazol; analysis of variance; animal experiment; animal model; animal tissue; arterial pressure; body weight; controlled study; drug potentiation; flow rate; fluid intake; histopathology; lateral brain ventricle; male; nonhuman; quadriceps femoris muscle; rat; salivation disorder; Animalia; Gossypium hirsutum